ANALISIS YURIDIS KEWENANGAN JAKSA DALAM PENEGAKAN HUKUM TINDAK PIDANA INFORMASI DAN TRANSAKSI ELEKTRONIK - Altansa, Fadlil; Rahmat, Diding (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
This research examines the authority of prosecutors in enforcing law in Indonesia against crimes that use electronic information and transactions. Along with the development of information technology, criminal acts in cyberspace are increasingly complex and require special handling. The main focus of this research is to analyze the legal basis that grants authority to prosecutors, the mechanism for implementing this authority, and the challenges faced in the law enforcement process. The research method used is normative juridical with an analytical approach to relevant laws and regulations. The research results show that although prosecutors have fairly clear authority based on law, implementation in the field still faces various obstacles such as limited human resources who are experts in the field of cyber law, as well as technical challenges in collecting and proving electronic evidence. This research recommends increasing the capacity and skills of prosecutors as well as inter-agency collaboration for the effectiveness of law enforcement in the digital realm.